Clinical academic careers for general practice nurses: a qualitative exploration of associated barriers and enablers. (November 2021) - Jones, Sarahjane; Bradbury, Andrew; Shortland, Sue; Hewett, Fraser; Storey, Karen
Background: The delivery of research in healthcare in the UK is dependent on a subgroup of clinicians – clinical academics – who concurrently engage in clinical practice and academic activities. The need to increase access to such roles for general practice nurses has been identified, although the need for a robust career framework remains. Aims: This study, with a qualitative interview and focus group design, aimed to explore the concept of clinical academic careers for general practice nurses by identifying barriers and enablers associated with pursuing and performing such roles. Methods: General practice nurses ( n  = 18) and general practitioners ( n  = 5) engaged in either an audio -recorded interview or focus group. Verbatim transcripts were subjected to thematic analysis. Results: Four themes were identified: awareness and understanding; career pathway; personal and professional attributes; and organisational factors. Awareness and understanding were generally poor. Participants suggested that the career pathway was unclear, although it was generally assumed that such roles were 'out of reach' and require a minimum of Master's level education. An interest in research and the confidence to perform such duties were reported as the required personal and professional attributes. Organisational factors included the need for employers to understand the value and benefit of general practice nurse clinical academic roles, along with ensuring that the inevitable competing demands of such a role were appropriately managed. Conclusions: This study highlights the difficulties faced by general practice nurses wishing to pursue a clinical academic career. Academia is seemingly placed on a pedestal, emphasising the need to embed research training early in nursing education to alter general practice nurse perceptions that clinical academic roles are unobtainable. The development of a robust career pathway for general practice nurse clinical academic roles may have a positive impact on the retention of experienced general practice nurses and attract newly qualified nurses. This research provides evidence as to the need for one.